Behaviour of precast hybrid steel/concrete joints - Guah, Eng Hock. (2008)
The research work in this thesis consists of two major parts. Firstly, the loadcarrying mechanism of the composite beams was explained using an "arch mechanism". The moment-rotation relationship of the composite joint was modelled using an "component approach". It is a well-known fact that the idealisations of either fully pin or fully rigid connection behaviour is truly uneconomical though it facilitates the analysis process.